Contrast Volume to Cystatin C-Based Glomerular Filtration Ratio Predicts the Risk of Contrast-Induced Nephropathy After Cardiac Catheterization. (March 2017) - Zhao, Jian-bin; Liu, Yong; Wu, Deng-xuan; Chen, Ji-yan; Duan, Chong-yang; Chen, Shi-qun; Tan, Ning
Cystatin C is considered to be a better alternative to creatinine for estimating glomerular filtration rate (GFR). The aim of this study was to investigate whether a contrast volume to estimated GFR based on cystatin C (V/eGFRcys) is a better predictor of contrast-induced nephropathy (CIN). We enrolled 1195 consecutive patients undergoing elective cardiac catheterization. Receiver–operating characteristic (ROC) curves were used to identify the optimal cutoff value of V/eGFRcys for detecting CIN. Multivariate regression models were used to evaluate whether V/eGFRcys is an independent risk factor for CIN. A total of 19 (1.6%) patients developed CIN. There was a significant association between a higher V/eGFRcys ratio and CIN risk ( P = .008). A ROC curve analysis indicated that a V/eGFRcys ratio of 2.29 was a fair discriminator for CIN. After adjusting for other known CIN risk factors, V/eGFRcys ratios >2.29 remained significantly associated with CIN (odds ratio = 2.93, 95% confidence interval: 1.02-8.44, P = .047). In conclusion, a V/eGFRcys >2.29 was a significant and independent predictor of CIN after cardiac catheterization.